Characterisation of chlorinated, brominated and mixed halogenated dioxins, furans and biphenyls as potent and as partial agonists of the Aryl hydrocarbon receptor - Wall, Richard J.; Fernades, Alwyn; Rose, Martin; Bell, David R.; Mellor, Ian R. (Elsevier, 2015)
The Aryl hydrocarbon receptor (AhR) binds a variety of chlorinated and brominated dioxins, furans and biphenyls. Mixed halogenated variants have been recently identified in food at significant levels but full characterisation requires potency data in order to gauge their impact on risk assessment. Rat H4IIE and human MCF-7 cells were treated with various mixed halogenated ligands. Antagonist properties were measured by treating cells with various concentrations of TCDD in the presence of EC25 of the putative antagonist. Measurement of CYP1A1 RNA was used to quantify the potency of agonism and antagonism. The PXDDs were found to be slightly less potent than the corresponding fully chlorinated congeners with the exception of 2-B,3,7,8-TriCDD which was 2-fold more potent than TCDD. PXDFs and non-ortho-PXBs were found to be more potent than their chlorinated congeners whilst several mono-ortho-substituted PXBs were shown to have partial agonistic properties. REPs were produced for a range of mixed halogenated AhR-activating ligands providing a more accurate estimation of potency for risk assessment. Several environmentally abundant biphenyls were shown to be antagonists and reduce the ability of TCDD to induce CYP1A1. The demonstration of antagonism for AhR ligands represents a challenge for existing REP risk assessment schemes for AhR ligands.